405 MINOCYCLINE THROUGH SUPPRESSION OF CYTOCHROME C AND DIABLO RELEASE ATTENUATES MALE GERM CELL APOPTOSIS AFTER HORMONE WITHDRAWAL. (1st January 2005) - Castanares, M.; Vera, Y.; Nunez, C.; Atienza, V.; Lue, Y.; Wang, C; Swerdloff, R. S.; Hikim, Sinha A.P.
Abstract : Minocycline is broadly protective in neurologic disease models featuring cell death and is being evaluated in clinical trials. Whether it also protects non-neuronal cells or tissues is not known. The purpose of the present study was to determine the therapeutic efficacy of minocycline, which effectively inhibits caspase activation in preventing or attenuating male germ cell apoptosis after withdrawal of gonadotropins and intratesticular testosterone (T). Groups of 5 adult (60 days old) male SD rats received one of the following treatment daily for 5 days: i) daily sc injection of gonadotropin-releasing hormone antagonist (GnRH-A), ii) oral administration of 30% gum acacia as a vehicle control, and iii) GnRH-A + oral administration of 50 or 100 mg/kg BW of minocycline. Rats were killed 5 days after treatment. Germ cell apoptosis was detected by TUNEL assay and quantitated as number of apoptotic germ cells per 100 Sertoli cells at stages VII-VIII. GnRH-A treatment for 5 days led to a significant (P ≤0.001) increase (108.1 ± 7.4) in the mean incidence of germ cell apoptosis exclusively at stages VII-VIII, when compared to controls, where no apoptosis was detected. Minocycline at both 50 and 100 mg dose levels significantly (P ≤0.001 prevented GnRH-induced germ cell apoptosis by 59.4% and 62.2%, respectively and fully prevented PARP cleavage. We also found that minocycline-mediated protection occurred at the mitochondria, involving the suppression of cytochrome c and DIABLO release. These results suggest that oral administration of minocycline is effective in protecting male germ cell apoptosis triggered after hormone withdrawal. Clearly, one implication of this observation is that minocycline can protect testicular germ cells not only by inhibiting caspase activation by suppressing cytochrome c release, but also augmenting the inhibitory effects of inhibitor of apoptosis proteins (IAPs) by suppressing the DIABLO release. Minocycline, with its proven clinical safety, capability to cross the blood-testis barrier, may become an effective therapy for acute testicular injury associated with increased germ cell apoptosis. Supported by NIH grants HD39293 and GM 08863.